Collaborative Governance dalam Pengembangan Gig Economy di Kota Padang - Muhammad Taufik Riyadi; Fitri Eriyanti (Policy, Law and Political Research Center, 2025)
This study analyzes the collaborative governance in the development of the gig economy in Padang City, as well as identifying its supporting and inhibiting factors. Using a descriptive qualitative method, data was collected through interviews, observations, and documentation from the Department of Manpower and Industry (DISNAKERIN), the Department of Cooperatives and UMKM (DISKOP & UMKM), and gig workers. The results show that collaborative governance has begun through the active role of local government as a facilitator and accelerator, evident from relevant job training programs, business guidance, digital marketing support, and facilitation of capital access. However, the involvement of non-governmental actors such as academics and NGOs in policy formulation is still limited, and long-term formal collaboration structures need to be developed. Key supporting factors include government initiatives, the attractive flexibility of gig work, and the utilization of digital technology and networks. Meanwhile, inhibiting factors include regulatory uncertainty and platform policies that disadvantage workers, lack of legal and social protection, operational and economic constraints for gig workers, limited local government budgets, and low digital literacy among UMKM and marginalized communities. This study concludes that strengthening cross-sector collaboration, formulating more comprehensive regulations, and improving digital literacy are crucial for creating an inclusive and sustainable gig economy ecosystem in Padang City.